(untitled) (Journal of International Studies, 2022)
Malaysia and Indonesia have taken a soft border approach to govern their Tebedu-Entikong border regions. Both governments have open but controlled customs, immigration, and quarantine facilities to manage cross-border movement of people, goods, and capital. Unfortunately, the ongoing cross-border governance was challenged by a non-traditional security threat, i.e., the COVID-19 pandemic that began in early 2020. The pandemic has the potential to impede the implementation of bilateral border policies which could jeopardize the efforts of the Socio-Economy of Malaysia-Indonesia Committee (Sosek Malindo) to effectively integrate both economies in the border region since its inception in 1985. In relation to this context, this paper aims to: (i) evaluate the challenges/impact of the COVID-19 pandemic and outstanding border issues on trade and development in the Entikong-Tebedu border region; and (ii) assess the role of Sosek Malindo in promoting greater integration and seamless connectivity in the Entikong-Tebedu border region. This paper presents a case-study on the Entikong-Tebedu border region and draws its observations and findings from inferences and interpretation of data collected from officials and other credible sources. Desk research was conducted on reports of Sosek Malindo meetings and research materials. Fieldwork was also conducted to observe the socioeconomic development status at the location of interest. The evaluation and assessment can be a reference point to reformulate cross-border governance policies that are characteristically a win-win solution for both parties by guaranteeing national security without compromising the socioeconomic development of the border region.